Evaluation of Therapeutic Management of Severe Heart Failure by Leg Isometric Exercise (LIE) Test - Ghose, Triptish Chandra; Yunosov, Zakir Zahidovich (University Heart Journal, 2008)
To evaluate the therapeutic management of severe heart failure by using Leg Isometric Exercise (LIE) test, a study was carried out in the Department of New Method Diagnosis of Cardiovascular Diseases of the Scientific Research Institute of Cardiology, Tashkent, Former USSR during the period of July 1990 to October 1992. Study was done on 32 male patients of severe heart failure who have significantly reduced tolerability to the physical exercise. All of them are within the age of 32 to 65 years (mean age 50.3+1.7 years). According to the functional status of these patients corresponds with functional class-II (n=12), FC-III (n=20) of NYHA. With the help of clinical evaluation and the results of repeated Echocardiography, which was conducted for evaluation of clinical effect in 10-12 days of starting of treatment, the patients were divided into two groups. Gr.-I (n=23) patients with significant clinical therapeutic effect and Gr.-II (n=9) - patients without significant clinical therapeutic effect. It was revealed that parameter like exercise DBP decreased distinctly (p<0.05) in gr.I patients and resting DSC (p<0.001) and exercise DSC (p<0.001) after starting of treatment in relation to initial stages at rest and exercise. Therefore signs of clinical therapeutic effect of patients with severe heart failure were decrease of resting DSC and exercise DSC and also decrease of exercise DBP. It is to be noted that these parameters can be utilized by cardiologist in their practice for predicting therapeutic effect of patients with severe HF on the basis of the results of repeated LIE test. (University Heart Journal 2007; 3 : 67-72 )